2018
DOI: 10.14214/sf.9940
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic approach of associated fungi with <i>Megaplatypus mutatus</i> (Coleoptera: Platypodinae)

Abstract: Highlights• There were no significant effects of host plant and location on fungal richness.• Two fungal species, belonging to Fusarium and Candida genera, were present in all the studied associations.• Results suggest that host plant identity would not be crucial to determine the composition of fungal communities associated to Megaplatypus mutatus. AbstractMegaplatypus mutatus is a major forest pest in Argentina and an emerging pest in Europe. In this study the multitrophic interactions between M. mutatus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Miller et al [33] reported that 435 OTUs were obtained from T. piniperda. Because extensive data filtering can potentially skew species composition, OTU numbers between this study and previously studies cannot be readily compared, but certain types of fungal-community composition were similar; for example, yeast and ophiostomatoid fungi were abundant and frequent among bark beetle species [14,31,33].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Miller et al [33] reported that 435 OTUs were obtained from T. piniperda. Because extensive data filtering can potentially skew species composition, OTU numbers between this study and previously studies cannot be readily compared, but certain types of fungal-community composition were similar; for example, yeast and ophiostomatoid fungi were abundant and frequent among bark beetle species [14,31,33].…”
Section: Discussionmentioning
confidence: 91%
“…However, the traditional approaches of analyzing fungal communities are limited in throughput and affected by methodological biases of culture-based techniques, which could lead to biases in fungal-diversity characterization due to the low number of isolates recovered. By comparison, the application of next-generation sequencing technologies, such as high-throughput sequencing (HTS), can overcome these limitations and thus help reveal a higher taxonomic diversity and richer fungal-community structure associated with bark beetles [6,14,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%